Spirituality and Heritage of Tradition: Exploring the Rujakan Pari Tradition in Blitar Regency - Melani, Zuanti Fitria; Sa'adillah, Aldho Efbinawan (IAIN Palangka Raya, 2024)
The tradition of rujakan pari among the people of Blitar Regency is an expression of farmers' gratitude for the previous harvest, as well as a request to avoid pest attacks and get an abundant harvest in the current planting season. The research aimed to find out the spirituality of the rujakan pari tradition in Blitar Regency. The research was qualitative research with a type of field research. Data collection methods were carried out through observation, interviews, and documentation. An anthropological approach was employed using Ferdinand De Saussure's semiotic theory and cultural ethnography theory. The findings showed that the ritual procession of the rujakan pari tradition is organized by the local village government involving different village residents with similar traditions in other areas. The Islamic values and philosophical meanings of the rujakan pari tradition are a way to foster community solidarity, which was seen in this ritual.